Overview of the bird diversity in oak (Quercus spp.) forest habitats in Isparta province, southwestern Turkish Anatolia - Adam BERGNER; Ogün Çağlayan TÜRKAY; Hasan ERYİĞİT; Mustafa AVCI (Turkish Journal of Forestry, 2018)
Natural and semi-natural oak (Quercus spp.) forests in Turkey are rich ecosystems of high conservation value that are increasingly threatened by logging and transformation into coniferous plantations. They harbor a diverse fauna and flora, but the current knowledge of their associated biodiversity is limited for many groups of organisms. In this paper, we present our preliminary results from inventories of the birds inhabiting various oak forests located in Isparta province in southwestern Turkish Anatolia. The bird species diversity was assessed both quantitatively and a qualitatively using random observation walks and fixed-radii point counts in 17 oak forests ranging in mean age from 30 years up to 300 years. A total of 52 bird species belonging to 43 genera and 24 families were identified. The three most abundant species were Eastern Bonelli’s Warbler (Phylloscopus orientalis), Common Chaffinch (Fringilla coelebs) and Common Blackbird (Turdus merula). Birds of national or international conservation concern are highlighted. Furthermore, we present an updated taxonomical species checklist.